2020
DOI: 10.1111/nmo.13984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbal preparation STW 5‐II on in vitro muscle activity in the guinea pig stomach

Abstract: Background STW 5 is a combination of nine medicinal herbal extracts and used to treat functional gastrointestinal disorders including functional dyspepsia. It has a region‐specific effect by relaxing the proximal and contracting the distal stomach. The research combination STW 5‐II (Iberogast® Advance) lacks three herbal extracts but seems clinically as effective as STW 5. However, the action of STW 5‐II on gastric motility is unknown. Methods In vitro circular and longitudinal muscle tone and contractility we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Previous in vitro studies have shown that STW5 has a region-specific effect on gastric motility by relaxing the proximal stomach and increasing antrum contractility. 8,18,19 This region-specific effect was also described by Pilichiewicz et al, 7 who studied 29 healthy volunteers and found that STW5 increased proximal gastric volume while increasing antral pressure waves. These findings may suggest a mechanistic rationale for STW5.…”
Section: Discussionsupporting
confidence: 74%
“…Previous in vitro studies have shown that STW5 has a region-specific effect on gastric motility by relaxing the proximal stomach and increasing antrum contractility. 8,18,19 This region-specific effect was also described by Pilichiewicz et al, 7 who studied 29 healthy volunteers and found that STW5 increased proximal gastric volume while increasing antral pressure waves. These findings may suggest a mechanistic rationale for STW5.…”
Section: Discussionsupporting
confidence: 74%
“…A mechanistic explanation of the efficacy of STW 5‐II in relieving postprandial distress symptoms may be its effect on sensory afferent neuronal signaling from the GI tract to the central nervous system, reducing stimuli for visceral hypersensitivity 35 . Furthermore, region‐specific effects of relaxing the proximal stomach and increasing contractility in the antrum have been described for STW 5‐II, 14 offering another possible mechanistic explanation for the short‐term efficacy of STW 5‐II. The broad anti‐inflammatory effects 12,15–17 described for STW 5‐II could explain the clinical efficacy seen over the 8‐week period, potentially acting against the low‐grade duodenal and gastric inflammation that have been posited as a potential mechanism underlying FD 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…STW 5‐II contains only six herbal extracts ( Iberis amara , Carum carvi , Glycyrrhiza glabra , Matricaria chamomilla , Melissa officinalis , and Mentha piperita ). In pharmacological studies, STW 5‐II and its herbal components have shown a broad spectrum of mechanistic actions, including anti‐inflammatory effects, mucosal protection, and modulation of upper GI tract motility 12–17 . Placebo‐ and active‐controlled clinical studies in FD patients have yielded clinical evidence for the efficacy of STW 5‐II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies have demonstrated that STW 5-II affects multiple targets, explaining its clinically proven efficacy in relieving FD-related symptoms [10][11][12][13]. One investigation showed that STW 5-II has a dual mode of action on gastric motility, i.e., by relaxing the gastric fundus and corpus and toning the antrum [14]. Additional mechanisms of action include the desensitization of hypersensitive afferents [15] and broad anti-inflammatory effects through normalizing histological parameters of inflammation [16] and reducing the levels of several proinflammatory chemokines [17][18][19].…”
Section: Introductionmentioning
confidence: 99%